Enhancing community integration after incarceration: findings from a prospective study of an intensive peer support intervention for veterans with an historical comparison group - Justeen Hyde; Thomas Byrne; Beth Ann Petrakis; Vera Yakovchenko; Bo Kim; Graeme Fincke; Rendelle Bolton; Christy Visher; Jessica Blue-Howells; Mari-Lynn Drainoni; D. Keith McInnes (BMC, 2022)
Abstract Background The transition to the community after incarceration presents challenges for returning citizens, including the immediate need to secure housing, employment, and income. Additionally, health care is essential for this population due to high rates of chronic physical health and mental health problems and substance use disorders. There is growing recognition of the need for interventions that support returning citizens as they navigate community reintegration while simultaneously tending to physical and behavioral health needs. We developed and pilot tested a peer support intervention designed to provide social, emotional, and logistic support and promote linkage and engagement in healthcare for returning citizens. We tested the intervention with US military veterans in Massachusetts who were being released from prison and jail. Outcomes related to linkage to and engagement in healthcare were evaluated using an historical comparison group. Engagement in peer support, housing status, and reincarceration rates were monitored for the intervention group. Results There were 43 veterans in the intervention group, and 36 in the historical comparison group. For linkage to primary care within 90 days of release, there were no statistically significant differences between the intervention and comparison groups (58% versus 67%). Intervention participants were significantly more likely to receive substance use treatment than the comparison group (86% versus 19%, p < .0001) and the mean monthly substance use visits was greater in the intervention group (0.96 versus 0.34, p < .007). Engagement in mental health services was greater for the intervention group than the comparison group (93% versus 64%, p < .003). There were no significant differences between groups for emergency department use and hospitalization. At the end of the study period, the majority of intervention participants who had been released for over a year were living in permanent housing (84%). Recidivism among the was low, with 7% re-arrested during the study period. Conclusions Augmenting reentry support through intensive peer support appears to have substantial benefits for veterans in terms of engaging them in health care and contributing to their longer-term stability, including housing and recidivism. Flexible reentry support such as this intervention may be well suited to meet the widely varying needs of returning citizens.